Improved mobility of the copper phthalocyanine thin-film transistor - Yakuphanoğlu, Fahrettin; Caglar, Mujdat; Caglar, Yasemin; Ilican, Saliha (Elsevier Science Sa, 2010)
Copper phthalocyanine (CuPc) organic thin-film transistor (OTFT) was fabricated by thermal evaporation deposition on p-SiO2 dielectric layer. Organic thin-film transistors used in large display areas need the enhancement of transistor performances by increasing the I-on/I-off ratio and the mobility. The output and transfer characteristics of CuPc-OTFF having source/drain interdigitated-finger geometry were investigated. The mobility, I-on/I-off ratio and inverse sub-threshold slope for the CuPc-OTFT were found to be 5.32 x 10(-3) cm(2) V-1 s(-1), 1.94 x 10(4) and 2.5 V/decade, respectively. The interface state density of the transistor was found to be 3.73 x 10(11) eV(-1) cm(-2) using the conductance-frequency method. The CuPc film indicated a homogeneous surface having 3.878 nm small roughness values as observed by atomic force microscope (AFM) measurements. The obtained results indicate that we have improved a CuPc-OTFT transistor with high mobility without being of any substrate treatment. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Organic thin-film transistor; Copper phthalocyanine; Thermal evaporation